Current Status of Immunotherapy for Localized and Locally Advanced Renal Cell Carcinoma. (1st April 2019) - Ghali, Fady; Patel, Sunil H.; Derweesh, Ithaar H.
Abstract : Systemic therapy strategies in the setting of localized and locally advanced renal cell carcinoma (RCC) have continued to evolve in two directions: as adjuvant therapy (to reduce risk of recurrence or progression in high risk localized groups), or as neoadjuvant therapy as a strategy to render primary renal tumors amenable to planned surgical resection in settings where radical resection or nephron-sparing surgery was not thought to be safe or feasible. In the realm of adjuvant therapy, the results of phase III randomized clinical trials have been mixed and contradictory; nonetheless based on the findings of the landmark S-TRAC study, the tyrosine kinase inhibitor Sunitinib has been approved as an adjuvant agent in the United States. In the realm of neoadjuvant therapy, presurgical tumor reduction has been demonstrated in a number of phase II studies utilizing targeted molecular agents. The advent of immunomodulation through checkpoint inhibition as first line therapy for metastatic RCC represents an exciting horizon for adjuvant and neoadjuvant strategies. This article reviews the current status and future prospects of adjuvant and neoadjuvant immunotherapy in localized and locally advanced RCC.